2017
DOI: 10.5507/fot.2017.007
|View full text |Cite
|
Sign up to set email alerts
|

Two new Tursiocola species (Bacillariophyta) epizoic on green turtles (Chelonia mydas) in French Guiana and Eastern Caribbean

Abstract: Abstract:Scrapings from several juvenile Chelonia mydas linnaeus (green turtle) from Eastern Caribbean and adults from French Guiana allowed for the description of two small and relatively rare epizoic Tursiocola species (Bacillariophyta). Differences with the other eight Tursiocola species previously described are discussed here. Particular attention is given to the cingulum of the two new species and a conceptual key is proposed for Tursiocola species, based on the cingulum structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…which we consider potentially new to science (Kaleli et al in preparation). Representatives of Chelonicola and Tripterion have been described and observed as obligately epizoic forms on seaturtle carapaces from oceanic waters (Majewska et al, 2015a;Riaux-Gobin et al, 2017a;Riaux-Gobin et al, 2017b) and have not yet been found on other substrates. Achnanthes elongata was described from samples from the Pacific coasts and with this study observed for the first time in the Mediterranean Sea, O. seblae has only been observed in the Mediterranean Sea (Kaleli et al, 2018).…”
Section: Epizoic Diatomsmentioning
confidence: 99%
See 3 more Smart Citations
“…which we consider potentially new to science (Kaleli et al in preparation). Representatives of Chelonicola and Tripterion have been described and observed as obligately epizoic forms on seaturtle carapaces from oceanic waters (Majewska et al, 2015a;Riaux-Gobin et al, 2017a;Riaux-Gobin et al, 2017b) and have not yet been found on other substrates. Achnanthes elongata was described from samples from the Pacific coasts and with this study observed for the first time in the Mediterranean Sea, O. seblae has only been observed in the Mediterranean Sea (Kaleli et al, 2018).…”
Section: Epizoic Diatomsmentioning
confidence: 99%
“…Although epizoic diatoms on vertebrates were first described from cetaceans, freshwater and sea turtles can also host very specific diatom floras ( Nemoto, 1956 ; Holmes, Nagasawa & Takano, 1993a ; Holmes, Nagasawa & Takano, 1993b ; Denys, 1997 ; Riaux-Gobin et al, 2017a ; Riaux-Gobin et al, 2017b ). Loggerhead sea turtles ( Caretta caretta Linnaeus, 1758) are one of the seven species of sea turtles ( Lutz & Musick, 1997 ), distributed from tropical waters of the Indian and the Pacific Ocean to temperate waters of the Atlantic Ocean and the Mediterranean Sea ( Ernst, Barbour & Lovich, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the recent increased interest in diatom diversity on marine vertebrates [1][2][3][4] in general and sea turtles in particular [5][6][7][8][9][10], a considerable number of sea turtle-associated diatom taxa have been described within the last five years [11][12][13][14][15][16][17][18][19][20][21][22][23][24] and it became clear that diatoms constitute an important element of the sea turtle epi-microbiome on both juvenile and adult individuals. Several sea turtle-associated diatom species have thus far only been reported from this substratum, suggesting a very close, even possibly obligatory relationship between the sea turtle-associated diatoms and their hosts.…”
Section: Introductionmentioning
confidence: 99%